Change in self-construal: a repertory grid technique study of women admitted to a Mother and Baby Unit - Wozniak, Eleanor E.; Hare, Dougal Julian; Gregg, Lynsey; Wittkowski, Anja (Frontiers in Psychiatry, 2024)
IntroductionPregnancy and the postnatal period represent a time of heightened risk for women to experience mental health difficulties. Some mothers may require specialist inpatient psychiatric support made available through Mother and Baby units (MBUs). Although there is evidence of the therapeutic benefits of MBUs, many studies have utilised methodologies vulnerable to interviewer and social desirability biases. The repertory grid technique (RGT), derived from personal construct theory (PCT), has been successfully used to explore how the way in which a person thinks about and defines the self (i.e., self-construal) changes following therapeutic intervention in samples of people experiencing mental health conditions. Therefore, this study aimed to explore change in maternal self-construal following MBU admission, utilising the RGT, thereby enhancing our understanding for the therapeutic role of MBU admissions in women’s mental health recoveries.MethodsParticipants were recruited from two MBUs in England. RGT was undertaken with participants shortly after admission and again at discharge, allowing for comparisons between grids to assess change in how a mother viewed herself in relation to certain aspects of the self (e.g., ideal self) and other people, a concept referred to as construing in PCT. Data were analysed using principal component analysis, Slater analysis, and content analysis.ResultsThere were 12 participants who completed repertory grids at admission, with eight (66.67%) participants also completing discharge grids. Most of the eight participants demonstrated improvements in overall self-esteem and self-esteem as a mother, a shift towards a more positive self-perception, and increased construed similarity between the self and positively construed others, and construing became more varied. Conversely, a few participants displayed a reduction in self-esteem, particularly in the maternal role and increased construed similarity between the self and negatively construed others, and construing became more rigid.ConclusionsAll participants exhibited changes to construing during their MBU admission, with most participants displaying positive changes to self-esteem and self-perception and a more adaptive process of construing. Potential implications are offered for service users, families, clinicians, and stakeholders. Recommendations for future research are also provided.